2011
DOI: 10.1097/hjh.0b013e328345023d
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction, platelet activation, thrombogenesis and fibrinolysis in patients with hypertensive crisis

Abstract: Hypertensive crisis with retinopathy confers a prothrombotic state characterized by endothelial dysfunction, platelet activation and increased thrombin generation, whereas fibrinolytic activity is enhanced. The observed changes in prothrombotic and antithrombotic pathways may contribute to the increased risk of ischaemic and haemorrhagic complications in this extreme hypertension phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 19 publications
2
28
0
5
Order By: Relevance
“…An important function of VWF is to mediate platelet-platelet interactions and platelet adhesion to sub-endothelial collagen and is associated with platelet consumption and thrombocytopenia [1315]. The median platelet count in patients with melioidosis was 189 × 10 9 /l compared to 299 × 10 9 /l in controls ( p = 0.0001, Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An important function of VWF is to mediate platelet-platelet interactions and platelet adhesion to sub-endothelial collagen and is associated with platelet consumption and thrombocytopenia [1315]. The median platelet count in patients with melioidosis was 189 × 10 9 /l compared to 299 × 10 9 /l in controls ( p = 0.0001, Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The plasma was stored at –70°C pending assay in The Netherlands. VWF antigen (Dako, Glostrup, Denmark) and VWF propeptide (Sanquin, Amsterdam, The Netherlands) were assayed by enzyme-linked immunoassay as described previously [15]. ADAMTS13 levels and prothrombin time (PT) were measured on an automated blood coagulation analyzer (BCS XP, Siemens Healthcare Diagnostics, Marburg, Germany) [26, 27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, serum aldosterone levels were found to be higher in MHT patients with TMA versus those without TMA [21]. In addition, hypertensive crises are known to be prothrombotic, leading to platelet aggregation, thrombin generation, and fibrinolysis [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Besides these mechanisms, a prothrombotic state may play a key role in hypertensive crisis; a recent, albeit small, study showed that sP-selectin was significantly higher in patients with hypertensive crisis compared with normotensive controls regardless of the presence of retinopathy, which suggests that platelet activation is a relatively early finding in the pathophysiologic sequelae of hypertensive crisis (11) (Figure 1). …”
Section: Pathophysiologymentioning
confidence: 99%